THE EFFECT OF REMOTE WORKING ON EMPLOYEES' ORGANIZATIONAL COMMITMENT WITH WORK-LIFE BALANCE AS A MEDIATOR - Bazi Puti Ayu Widyasana; Suryani Hardjo; Patisina (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the relationship between remote working, work-life balance, and organizational commitment among millennial employees. Remote working, which is increasingly popular due to its flexibility, was found to have a positive effect on work-life balance. Better work-life balance increases organizational commitment, reflecting employee loyalty and work motivation. Data were collected from 255 respondents through an explanatory quantitative method using snowball sampling. The results of the SEM-PLS analysis showed that remote working had a significant effect on work-life balance (13.5%) and organizational commitment (67.4%). Work-life balance also acted as a significant mediator between remote working and organizational commitment. This study emphasizes the importance of work flexibility in creating a work environment that supports work-life balance and increases employee loyalty.